1992
DOI: 10.3354/dao012121
|View full text |Cite
|
Sign up to set email alerts
|

Electrophcretic detection of proteases from different Flexibacter columnaris strains and assessment of their variability

Abstract: Proteases with apparent molecular weights of 47, 40, 34 and 32 kD were identified in cellfree extracellular products (ECP) of Flexibacter colurnnaris by using substrate SDS-polyacrylamide gel electrophoresis. Similar protease profiles were associated with ECP collected at intervals during several days in culture. Furthermore, the proteases produced by a collection of 13 F. colurnnaris isolates from a variety of fish species and geographic sources showed great uniformity but differed markedly from the protease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 17 publications
1
29
3
Order By: Relevance
“…Reductions in the erythrocyte count, hematocrit percentage and hemoglobin rate indicate that fish infected with the bacterium In mammals and fish, infectious diseases activate the cell immunological system, thereby changing the percentage of circulating blood cells that provide organic defense (7). For this reason, there is a need to identify and quantify blood cells for organic defense, in both healthy and diseased fish, in order to gain better understanding of cell participation in pathological processes.…”
Section: Resultsmentioning
confidence: 99%
“…Reductions in the erythrocyte count, hematocrit percentage and hemoglobin rate indicate that fish infected with the bacterium In mammals and fish, infectious diseases activate the cell immunological system, thereby changing the percentage of circulating blood cells that provide organic defense (7). For this reason, there is a need to identify and quantify blood cells for organic defense, in both healthy and diseased fish, in order to gain better understanding of cell participation in pathological processes.…”
Section: Resultsmentioning
confidence: 99%
“…psychrophilum grows at temperatures between 4 and 20°C. Using gel substrate electrophoresis, Bertolini et al (5) observed that an array of proteolytic enzymes were present and suggested that some of them were related to virulence. In this study we purified a protease and examined the physiological conditions under which this enzyme was produced.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, F. psychrophilum virulence has been associated with lipopolysaccharides (9), with the ability to lyse dead bacterial cells (48), and with the capacity of different strains to degrade chondroitin sulfate, collagen, or fibrinogen (24). The few studies done to date have related pathogenesis to the production of exocellular enzymes that degrade casein or gelatin (5) and elastin (38). Electrophoretic detection of proteases by substrate sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) for different F. psychrophilum strains showed that a relationship between proteolytic profile and virulence can be established (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The external symptoms caused by F. columnare infection, such as tissue lesions and erosion [40] reflect the importance of proteases for columnaris disease pathology. Indeed, proteolytic activities, including ability to degrade gelatin, casein, hemoglobin, fibrinogen and elastin, have been reported in F. columnare [4]. However, thus far only chondroitinase, an enzyme degrading chondroitin sulfates, the proteoglycan components of vertebrate connective tissues, has been connected to virulence of F. columnare [23,48,51].…”
Section: Discussionmentioning
confidence: 99%